An extension of nickel-catalyzed reductive coupling between tertiary alkyl halides with allylic carbonates. Issue 39 (27th September 2018) - Yu, Yingying; Chen, Haifeng; Qian, Qun; Yao, Ken; Gong, Hegui
Abstract: The nickel catalyzed reductive coupling of allylic carbonates with chloro-cyclotryptamine analogs to construct sterically congested all C(sp 3 ) quaternary centers has been achieved with emphasis on the substrate scope. And the using of dienyl methyleneyl carbonates coupling with a variety of tertiary alkyl halides furnished the dienylated products improved the reaction's applicability. Graphical abstract: Image 1